PREDICTION OF CARBON DIOXIDE EMISSION FROM ENERGY CONSUMPTION IN THAILAND WITH SARIMA-ANN-REG MODEL - Karseewong, Suteemon; Boonlha, Kanlaya (Srinakharinwirot University Journal of Sciences and Technology, 2024)
This study aims to forecast monthly CO2 emissions in Thailand using data from the Ministry of Energy using the model SARIMA-ANN-REG. Using linear regression model combined both SARIMA and Artificial Neural Network (ANN) approaches. Monthly CO2 emission data from January 2015 to December 2022 (96 months) as the training dataset, while data from January to July 2023 (7 months) was used for forecasting. The model selection was based on minimizing the root mean square error (RMSE). The result found that the SARIMA-ANN-REG model with SARIMA(1,0,2)(1,1,1)12 and the 8 hidden nodes in the ANN component, achieving an RMSE of 0.4992 on the training set. Applied to the forecasting period, the model yielded an RMSE of 1.2106 with the forecast model is where , , are the forecast value, forecast value using SARIMA mode and forecast value with ANN model at time, respectively.